Megavoltage conebeam CT cine as final verification of treatment plan in lung stereotactic body radiotherapy. Issue 3 (6th February 2016) - Kudithipudi, Vijay; Gayou, Olivier; Colonias, Athanasios
Abstract: Introduction: To analyse the clinical impact of megavoltage conebeam computed tomography (MV‐CBCT) cine on internal target volume (ITV) coverage in lung stereotactic body radiotherapy (SBRT). Methods: One hundred and six patients received lung SBRT. All underwent 4D computed tomography simulation followed by treatment via image guided 3D conformal or intensity modulated radiation. Prior to SBRT, all patients underwent MV‐CBCT cine, in which raw projections are displayed as beam's‐eye‐view fluoroscopic series with the planning target volume (PTV) projected onto each image, enabling verification of tumour motion relative to the PTV and assessment of adequacy of treatment margin. Results: Megavoltage conebeam computed tomography cine was completed 1–2 days prior to SBRT. Four patients (3.8%) had insufficient ITV coverage inferiorly at cine review. All four plans were changed by adding 5 mm on the PTV margin inferiorly. The mean change in PTV volumes was 3.9 cubic centimetres (cc) (range 1.85–6.32 cc). Repeat cine was performed after plan modification to ensure adequate PTV coverage in the modified plans. Conclusions: PTV margin was adequate in the majority of patients with this technique. MV‐CBCT cine did show insufficient coverage in a small subset of patients. Insufficient PTV margins may be a function of 4D CT simulation inadequacies or deficiencies in visualizing the ITV inferior border in the full‐inhale phase. MV‐CBCT cine is a valuable tool for final verification of PTV margins.